Delay in hospital presentation is the main reason large vessel occlusion stroke patients do not receive intravenous thrombolysis - Ethan S. Brandler; Derek L. Isenberg; Joseph Herres; Huaqing Zhao; Chadd K. Kraus; Daniel Ackerman; Adam Sigal; Alexander Kuc; Jason T. Nomura; Susan Wojcik; Michael T. Mullen; Nina T. Gentile (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Intravenous thrombolysis (IVT) and endovascular therapy (EVT) are the mainstays of treatment for large vessel occlusion stroke (LVOS). Prior studies have examined why patients have not received IVT, the most cited reasons being last‐known‐well (LKW) to hospital arrival of >4.5 hours and minor/resolving stroke symptoms. Given that LVOS patients typically present moderate‐to‐severe neurologic deficits, these patients should be easier to identify and treat than patients with minor strokes. This investigation explores why IVT was not administered to a cohort of LVOS patients who underwent EVT. Methods This is an analysis of the Optimizing the Use of Prehospital Stroke Systems of Care (OPUS‐REACH) registry, which contains patients from 9 endovascular centers who underwent EVT between 2015 and 2020. The exposure of interest was the receipt of intravenous thrombolysis. Descriptive summary statistics are presented as means and SDs for continuous variables and as frequencies with percentages for categorical variables. Two‐sample t tests were used to compare continuous variables and the chi‐square test was used to compare categorical variables between those who received IVT and those who did not receive EVT. Results Two thousand forty‐three patients were included and 60% did not receive IVT. The most common reason for withholding IVT was LKW to arrival of >4.5 (57.2%). The second most common contraindication was oral anticoagulation (15.5%). On multivariable analysis, 2 factors were associated with not receiving IVT: increasing age (odds ratio [OR] 0.86; 95% confidence interval [CI] 0.78–0.93) and increasing time from LKW‐to hospital arrival (OR 0.45 95% CI 0.46–0.49). Conclusion Like prior studies, the most frequent reason for exclusion from IVT was a LKW to hospital presentation of >4.5 hours; the second reason was anticoagulation. Efforts must be made to increase awareness of the time‐sensitive nature of IVT and evaluate the safety of IVT in patients on oral anticoagulants.